IMPORTANCE OF MICROSCOPIC STOOL EXAMINATION IN PATIENTS WITH DIARRHOEA - Shah, Sajid Ali; Marwat, Safdar Ali; Rashid, Haroon Ur; Hussain, Altaf; Khurshid, Khurram; Ahmad, Sheraz (Journal of Ayub Medical College Abbottabad, 2014)
Background: Loose motion is a common symptom in patients reporting to our hospital. As it is a small set up where only facility for microscopic stool examination is available, we designed this study to know how much microscopic stool examination can help us in management of patients with diarrhoea. Methods: This cross-sectional descriptive study was conducted from January 2010 to April 2012, at Thall Scout Hospital, Hangoo, Khyber Pukhtoon Khwa, Pakistan. All the patients presenting with acute diarrhoea were included in the study. Patients older than 12 years of age were labelled as adults and those 12 years or younger as child. Stool specimens were collected using proper procedure and were examined microscopically. Results: Of 494 stool specimens examined, 117 (23.68%) were positive for parasites or their ova, 34 (6.88%) had numerous pus and red blood cells and 343 (69.43%) patients had only stool of loose/soft consistency. Of 117 stool specimens positive for parasites, Giardia lamblia was detected in 67 (57.26%) patients, Entamoeba histolytica in 22 (18.80%) patients, H. nana in 10 (8.55%) patients, Tenea saginata in 8(6.84%) patients, hook worm in 6 (5.13%) patients, ascaris in 2 (1.71%) and Trichuris trichura in 2 (1.71%) patients. Conclusion: Among the parasitic causes of diarrhoea, giardia is the most common cause in our study with entameoba the second most common cause. Keywords: Parasite, diarrhoea, protozoa, helminthes, Giardia lamblia